The system Tetrabothrius bassani (Tetrabothriidae)/Morus bassanus (Sulidae) as a bioindicator of marine heavy metal pollution - Mendes, Paula (2013)
Helminths are known to accumulate higher amounts of certain elements than their hosts. The present study assesses the accumulation of heavy metals in Tetrabothrius bassani and in its host, the Atlantic gannet (Morus bassanus) found dead due to bycatch along the seashore in the centre of Portugal. Samples of kidney, liver and pectoral muscle of 23 infected gannets, as well as specimens of T. bassani were analysed for As, Cd, Cr, Cu, Hg, Mn, Pb, Se and Zn by ICP-MS. The evidenced lower concentrations of Cr and Pb in tissues of gannets in comparison to an earlier study performed in the same area may reveal a change in the diet of M. bassanus between both study periods. The highest bioaccumulation factor was obtained for Cd with a 12.7-times higher concentration in the cestode than in gannet muscle. Lead concentration in T. bassani was 6.9-times higher than in kidney tissue, 8.5-times higher than in muscle and 9.5-times higher than in liver of M. bassanus. The cestode/seabird system T. bassani/M. bassanus can be considered a promising bioindicator system to monitor environmental Cd and Pb pollution in marine ecosystems.